Timing of Investment and International Expansion Performance in China - Luo, Yadong (Journal of International Business Studies, 1998)
This study examines the multivariate and univariate performance effects of timing of FDI in an emerging economy at the business unit level. A longitudinal analysis of industry-wide, firm-specific data on FDI timing and foreign venture performance in China reveals that timing has a significant influence on overall, as well as on individual, aspects of venture performance. It is observed that early entrants outperform late movers in terms of local market expansion and asset turnover, whereas late movers are superior to early entrants with regard to risk reduction and accounting return during the initial period of international expansion. Factor analysis confirms that the importance of timing in affecting FDI decisions is as significant as that of internalization, ownership, or location factors.